The Influence of Online Media on the Progress Prima Indonesia University - Betty; Syaifuddin; Sofyan Matondang (MANAGER: Journal of Management and Administration Science, 2024)
The establishment of universities and aggressive marketing strategies in the modern era of globalization have increased competition in the higher education sector. Therefore, it is very important to know the benefits of Royal Prima Universities' marketing strategies, both online and offline, by conducting research on how affiliate marketing as a moderating variable affects brand image. The aim of this research is to explain the synergy and interdependence that exists between offline and online marketing activities in the process of forming perceptions of a university. This will be achieved through analysis involving multiple scientific disciplines. With 300 students as a sample, the data was processed using the hair formula method. In path analysis, a hypothesis testing approach is used. The test results show that offline marketing has a greater impact ratio on affiliate marketing compared to online marketing. The results also show that offline marketing has a greater ratio impact on brand image than online marketing.